Integration Interval Determination in Transmitted Reference Pulse Cluster Systems for UWB Communications - Li Jin; Xiaodai Dong (2008 IEEE 68th Vehicular Technology Conference, 2008)
A recently proposed transmitted reference pulse cluster (TRPC) structure contains compactly spaced reference and data pulses, and enables a low complexity, robust and practical auto-correlation detector to be used at the receiver. TRPC has been shown to outperform the conventional transmitted reference and non-coherent pulse position modulation systems in ultra-wideband channels. Previous research indicated that the integration interval of the auto-correlation detector is critical to the performance of TRPC. In this paper, practical data-aided algorithms are introduced to determine the integration interval of the TRPC structure based on minimizing the system bit error rate. The proposed scheme is compared to the traditional threshold crossing method and demonstrates around 2 dB performance gain in IEEE 802.15.4a channels. A simplified version of the scheme valid for low signal to noise ratios is also presented. The proposed integration interval determination method does not require Nyquist rate sampling or analog averaging with symbol long delay lines, and is therefore suitable to practical implementation.